The Problem of Environmental Security of Russia - O. I. Bashlakova (Vestnik MGIMO-Universiteta)
The theme of the article is essentially relevant. Relevant because Russian environmental safety can be ensured only with a glance to the sustainable development. In order to make this happen the state's priorities should be altered from economic to ecological ones. The article clarifies the definition of environmental safety, identifies the place and role of environmental safety in the country's national security, discusses some of the issues of the environmental security in a state in today's ecological crisis, offers a mechanism to ensure environmental safety, reflects the need for a change in the perspective of decision-makers and different groups of citizens with the instruments of ecologically-oriented policy. Moreover, the author explains the necessity of environmental education for the implementation of the environmental security in Russia in terms of the sustainable development. The author points out that if the systems of nature and the appropriate quality of the environment remain in a proper balance, the sustainable development in the Russian Federation, the quality of life and health of its population, as well as national security will be ensured. The fact, that the National Security Strategy of the Russian Federation includes the issue of environmental safety and defines it as a safeguard of the sustainable development in the society and favorable living conditions, is a reflection of such understandings. The article underlines there is a need to develop a mechanism for improving the legal regulation in the sphere of environmental security in the country. In this regard, the author concludes that such a mechanism will be aimed at protecting the interests of citizens and their right to an ecologically safe environment. That objective implies that enterprises and organization of all forms of ownership should be economically motivated to use the environmentally acceptable technologies and, consequently, to improve the environment's condition. The author implies that the environmental security is an essential component of the state national security, which can become a nation-binding idea, that can unite the peoples of Russia.